HISTORICAL-PHILOSOPHICAL ASPECTS OF LEGAL CERTAINTY - Sargsyan, Ani (State and Law, 2025)
Within the framework of this scientific article, the author discussed the legal content of the terms “certainty of act”, “certainty of law”, “legal certainty”, “formal certainty of law”, “uncertainty of law”, “legal uncertainty”. The analysis was carried out on the basis of a comprehensive study of the works of a number of lawyer-scientists and philosophers G.F. Hegel and I. Kant. The author touched upon the problem of certainty and uncertainty of law, certainty of law and law-making activity, as well as the relationship with other principles of law. The author came to the conclusion that the certainty of law is. principle of law, an integral part of lawmaking process, a process directed to creating stable legislation, a means of proper implementation of law-enforcement activities, a guarantee directed to protecting human rights and obligations, a regulation directed to reviewing judicial acts, their entry into legal force, mandatory execution, uniformity and stability of judicial practice. At the same time, in the conditions of development of law, the principle of certainty of law should be considered not as an integral part of the principle of the rule of law, but as an independent, fundamental principle of law. The author examined the correlation of lawmaking and the certainty of law from two positions. In the first case,the lawmaking process is carried out in such a way that the forming legal acts comply with the principle of legal certainty. In the second case, already existing legal acts are “subjected” to certainty: ambiguities are eliminated, provisions are clarified, etc. The author came to the conclusion that the certainty of law in terms of the form of action can be divided into static - as a principle whose rules correspond to legal acts at the stage of formation, and dynamic - as a process as a result of which ambiguities and uncertainties in legal acts are overcome. In conclusion, the author established that the principle of certainty of law is a measure of the “flexibility” of legislation in the formation of stable legislation.